2015
DOI: 10.15740/has/arjci/6.2/66-72
|View full text |Cite
|
Sign up to set email alerts
|

Response of different wheat genotypes to different sowing time in relation to GDD accumulation

Abstract: : An experiment on response of different wheat genotype to different sowing time in relation to GDD accumulation was carried out in Rabi season of 2010-11 at the research field of Wheat Research Unit, Dr. Panjabrao Deshmukh Krishi Vidyapeeth, Akola (M.S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…On the other hand, the timely sown crop gets an advantage because after having completed its vegetative growth satisfactory it comes in the ear stage when the temperature is quite favourable. Deshmukh et al [37] and Bashir et al [38] also reported similar findings and stated that timely sowing gave higher test weight as compared to delayed sowing. Yields of wheat increased significantly when sowing of wheat on 15 th November which was statistically at par with sowing on 30 th November (Table 1.).…”
Section: Effect Of Varying Sowing Datesmentioning
confidence: 59%
“…On the other hand, the timely sown crop gets an advantage because after having completed its vegetative growth satisfactory it comes in the ear stage when the temperature is quite favourable. Deshmukh et al [37] and Bashir et al [38] also reported similar findings and stated that timely sowing gave higher test weight as compared to delayed sowing. Yields of wheat increased significantly when sowing of wheat on 15 th November which was statistically at par with sowing on 30 th November (Table 1.).…”
Section: Effect Of Varying Sowing Datesmentioning
confidence: 59%